(untitled) - Vega, Roberto; Morales, Regino Juan de Dios; Ofria, Humberto (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Estudio del contenido de alcoholes superiores en vinos de Mendoza (1964)

(untitled)
The present work is a Bibliographie review of alcohols wine contents, specially about those known as superiors. Has been used the KONAORWSKY and PENNIMAN analisys method, using for the lectures a KLETT SUMMERSON type fotocolorimeter and the type solutions concentration values obtained marked in a graphic proposing then a y : a.x type ecuation. In this way are determinated the superior alcohols expressed in mg. per cent of differents kinds of wines observed (whites, reds, pinks, and ele ar wines) and expressed as isobutyl and isoanyl alcohols and their relationship per cent of absolut ethylic alcohol. Has been stablisher the maximum, minimus and average contents for each type of wine and in general for wines of differents kinds ands sources.